2022
DOI: 10.1186/s13722-022-00288-4
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and experiences toward extended-release buprenorphine among persons leaving jail with opioid use disorders before and during COVID-19: an in-depth qualitative study

Abstract: Background Extended-release buprenorphine (XRB) offers a novel approach to sustained monthly treatment for people who use opioids in criminal justice settings (CJS). This study explores the experiences of adults receiving XRB as a jail-to-community treatment. Methods and findings In-depth qualitative interviews were conducted among adult participants with opioid use disorder (OUD; n  = 16) who were recently released from NYC jails and maintained on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Although preliminary, these findings suggest that monthly injectable extended-release buprenorphine is a useful OUD treatment option before and after release from jail. This conclusion is also supported by a recent series of in-depth qualitative interviews conducted among adult participants with OUD who were recently released from New York City jails and maintained on SUBLOCADE® after switching from daily sublingual buprenorphine-naloxone ( Cheng et al., 2022 ). SUBLOCADE® treatment during jail-to-community reentry was perceived by participants as a favorable treatment approach to reduce their risk of opioid reuse, illicit activities, stigma associated with daily receipt of MOUD, and COVID-19 exposure.…”
Section: The Regulatory Approval Of Buprenorphine For the Treatment O...mentioning
confidence: 70%
“…Although preliminary, these findings suggest that monthly injectable extended-release buprenorphine is a useful OUD treatment option before and after release from jail. This conclusion is also supported by a recent series of in-depth qualitative interviews conducted among adult participants with OUD who were recently released from New York City jails and maintained on SUBLOCADE® after switching from daily sublingual buprenorphine-naloxone ( Cheng et al., 2022 ). SUBLOCADE® treatment during jail-to-community reentry was perceived by participants as a favorable treatment approach to reduce their risk of opioid reuse, illicit activities, stigma associated with daily receipt of MOUD, and COVID-19 exposure.…”
Section: The Regulatory Approval Of Buprenorphine For the Treatment O...mentioning
confidence: 70%
“…Examples of such programs include mobile van settings 57 or telehealth buprenorphine clinics, which have been shown to be successful in catering to incarcerated individuals at reentry, 58,59 as well as the Transitions Clinic Network, a consortium of primary care clinics that aims to increase access to health care services among people recently released from incarceration. 60 Recent trials have also shown the potential promise of injectable forms of buprenorphine in facilitating treatment continuity following discharge, 6163 but uptake of these treatments in carceral settings has been slow.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research showed that treatment with buprenorphine improved treatment retention for OUD, so it is possible that better consistency in use among this group could be a contributor [ 22 ]. In addition, other studies have reported higher adherence among buprenorphine users, in part due to the lesser severity of opioid withdrawal symptoms when starting buprenorphine [ 23 , 24 ]. Buprenorphine has been shown to be equivalent to methadone in alleviating the severity of opioid withdrawal, but symptoms may resolve more quickly [ 25 ].…”
Section: Discussionmentioning
confidence: 99%